Boosting post-harvest quality of 'Coscia' pears: Antioxidant-enriched coating and MAP storage - Ilenia Tinebra; Roberta Passafiume; Alessandra Culmone; Eristanna Palazzolo; Giuliana Garofalo; Vincenzo Naselli; Antonio Alfonzo; Raimondo Gaglio; Vittorio Farina (AIMS Agriculture and Food)
This study investigated the effects of combining an edible coating (EC) formulation with modified atmosphere packaging (MAP) on the postharvest quality of Coscia pears (Pyrus communis L.). The EC formulation consisted of Aloe vera gel, hydroxypropyl methylcellulose (HPMC), ascorbic acid, and citric acid. Pears were sliced and subjected to three treatments: untreated (CTR), EC with MAP1 (70% CO2 + 30% N2), and EC with MAP2 (30% CO2 + 70% N2). Physicochemical, microbiological, and sensory analyses, as well as assessments of proximate compounds and vitamin content, were conducted over a 9-day storage period at 4 ± 1 ℃ and 90% ± 5% relative humidity. The results showed that combining EC with MAP significantly reduced juice leakage, delayed browning, and preserved firmness compared to untreated samples. Additionally, MAP treatments, particularly MAP2, improved color stability by minimizing both aerobic and anaerobic respiration. Sensory evaluations indicated that treated samples had superior visual appearance and texture. Microbiological analyses confirmed that all samples maintained high hygienic standards throughout the storage period. Furthermore, mineral and vitamin content analyses demonstrated that EC and MAP treatments helped retain essential nutrients in the pear slices. In conclusion, the combination of EC and MAP effectively extended the shelf-life and preserved the nutritional quality of fresh-cut Coscia pears, offering substantial benefits for both consumers and the food industry.